Targeted Training in Managing Children With Poor Trunk Control: 4 Case Reports. Issue 2 (April 2018) - Pin, Tamis W.; Butler, Penelope B.; Shum, Sandra Lai-Fong
Abstract : Purpose: This study investigated whether targeted training was feasible with young children younger than 2 years with poor trunk control due to cerebral palsy or developmental delay without using specialized equipment and the overall change in trunk control and functional ability, with the addition of targeted training to standard care physical therapy. Summary of Key Points: Four children younger than 24 months with motor disorders were recruited. No difficulty was identified in using targeted training with this group. Within 3 months of commencing intervention, the 4 children had increased trunk control and functional abilities including independent sitting and bilateral hand use in play. Conclusions and Recommendations for Clinical Practice: This form of targeted training was feasible for young children with motor disorders and augmented standard care therapy in enhancing both trunk control and motor skills. Targeted training should be further investigated as a potentially effective treatment. Abstract : This study investigated the overall change in trunk control and functional ability with the addition of targeted training to standard care physical therapy.